2019
DOI: 10.2147/cmar.s202225
|View full text |Cite
|
Sign up to set email alerts
|

<p>Dihydrodiosgenin inhibits endothelial cell-derived factor VIII and platelet-mediated hepatocellular carcinoma metastasis</p>

Abstract: Background: Our previous studies have demonstrated that diosgenin and diosgenin derivatives exhibit excellent antithrombotic activity via regulating platelet function and coagulation factor level. Platelets and blood coagulation system are highly associated with tumor hematogenous metastasis. Therefore, the purpose of this study was to evaluate whether dihydrodiosgenin (dydio) mediated-platelet inhibition or coagulation factor level modulation is involved in hepatocellular carcinoma cell (HCC) metas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 60 publications
1
12
0
Order By: Relevance
“…In vivo and in vitro studies on melanoma and breast cancer metastasis have shown that platelets activate the coagulation cascade by secreting thrombin and tissue factor, which results in a meshwork of platelets and fibrin shielding tumor cells and allows them to escape immune-surveillance and successfully invade distant sites [29,33]. A recent paper by Zhuang et al, shows evidence that this process also occurs in a metastatic HCC-mouse model [34]. They found that activated platelets adhere to tumor cells and that pharmacological inhibition of platelet activation, with diosgenin and diosgenin derivates, inhibits platelet adherence to tumor cells and decreases metastasis.…”
Section: The Effect Of Platelets On Hcc Proliferation and Metastasismentioning
confidence: 99%
See 1 more Smart Citation
“…In vivo and in vitro studies on melanoma and breast cancer metastasis have shown that platelets activate the coagulation cascade by secreting thrombin and tissue factor, which results in a meshwork of platelets and fibrin shielding tumor cells and allows them to escape immune-surveillance and successfully invade distant sites [29,33]. A recent paper by Zhuang et al, shows evidence that this process also occurs in a metastatic HCC-mouse model [34]. They found that activated platelets adhere to tumor cells and that pharmacological inhibition of platelet activation, with diosgenin and diosgenin derivates, inhibits platelet adherence to tumor cells and decreases metastasis.…”
Section: The Effect Of Platelets On Hcc Proliferation and Metastasismentioning
confidence: 99%
“…They found that activated platelets adhere to tumor cells and that pharmacological inhibition of platelet activation, with diosgenin and diosgenin derivates, inhibits platelet adherence to tumor cells and decreases metastasis. In vitro studies have also shown a direct effect of platelet lysates on tumor cell migration and invasion, suggesting the pro-metastatic effect is not merely a result of avoiding immune-surveillance, but also due to the direct effect of their stored growth factors [16,34]. Platelets have also been reported to alter the response to chemotherapeutic agents.…”
Section: The Effect Of Platelets On Hcc Proliferation and Metastasismentioning
confidence: 99%
“…Furthermore, high platelet counts correlate with an increased risk of developing extrahepatic metastasis [ 116 ]—likely due to platelet-mediated cell growth, tumor aggressiveness and migration [ 117 ]. Moreover, platelet-mediated metastasis is prevented by the inhibition of coagulation factor FVIII, which plays a role in platelet-cancer cell interaction [ 118 ]. However, beside their proliferating effects, platelets also promote HCC cell apoptosis [ 105 ].…”
Section: Hepatocellular Carcinoma (Hcc)mentioning
confidence: 99%
“…Yang et al demonstrated that salvianolic acid A can block the secretion of glucose-regulated protein 78 (GRP78) to inhibit cancer-related angiogenesis [ 156 ]. Zhuang et al demonstrated that dihydrodiosgenin (DYDIO) can inhibit platelet activation and reduce endothelial cell-derived factor VIII (FVIII) to inhibit HCC metastasis [ 157 ].…”
Section: Microenvironment-specific Interventionsmentioning
confidence: 99%